Sensory Quality of Quail Eggs Fed with Coriander Flour (Coriandum Sativum Linn) in The Feed - Dewi Wahyuni; Deden Sudrajat (Indonesian Journal of Applied Research (IJAR), 2021)
One of the sources of animal protein for the community can be obtained from quail eggs. Quail eggs have nutritional value that is not inferior to other poultry eggs. Feed is one of the factors that can affect egg quality. Coriander is a spice that contains essential oils that are beneficial for the body when consumed. So it is hoped that the presence of this essential oil can help improve livestock growth and produce quality quail eggs sensory. This study aimed to examine the effect of giving coriander flour to quail feed on the sensory quality of eggs. The study was conducted for 30 days. The livestock used were Japanese quail aged 30 days with 100 heads. The feed used is commercial feed and additional coriander flour. The design used was a completely randomized design with 4 treatments and 5 replications for each unit of 5 birds with treatment R0 = commercial feed +0% coriander flour, R1 = commercial feed + 0.5% coriander flour, R2 = commercial feed + 1% coriander flour, R3 = commercial feed + 1.5% coriander flour. Data were analyzed using Kruskall Wallis and Duncan's multiple range test. The results showed that the administration of coriander flour had a significant effect (P<0.05) on the hedonic test of egg white color and texture hedonic quality test, while for the egg yolk color, taste, aroma variables were not significantly different (P>0.05). This study concludes that organoleptic administration of 1% coriander flour can increase the panelists' preference for egg whites and improve the texture of quail eggs.